2016
DOI: 10.4314/sajas.v46i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor 9 gene variants in Sudanese desert sheep ecotypes

Abstract: Certain variants in the growth differentiation factor 9 (GDF9) gene have major effects on the ovulation rate in sheep. The aim of this study was to analyse GDF9 variability in the Sudanese desert sheep ecotypes Ashgar, Dubasi and Watish, and to test identified variants for association with litter size. For this purpose, ewes of these ecotypes with litter size records for at least two litters were sampled. The complete GDF9 exon 2 was sequenced in a total of 28 ewes. An additional variant in exon 1 (c260G>A) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The GDF-9 gene is responsible for the external regulation factor in the production and secretion of oocytes and has an important role in the growth and differentiation of both follicles (folliculogenesis) at an early stage (as well as granulose cells) and (theca cells) in sheep ovaries [22,23]. The studies of [24][25][26][27][28][29][30], showed that mutations in the GDF-9 gene have direct effects on litter size by increasing the rate of ovulation.…”
Section: Values In Rows With Different Letters Differ Significantlymentioning
confidence: 99%
“…The GDF-9 gene is responsible for the external regulation factor in the production and secretion of oocytes and has an important role in the growth and differentiation of both follicles (folliculogenesis) at an early stage (as well as granulose cells) and (theca cells) in sheep ovaries [22,23]. The studies of [24][25][26][27][28][29][30], showed that mutations in the GDF-9 gene have direct effects on litter size by increasing the rate of ovulation.…”
Section: Values In Rows With Different Letters Differ Significantlymentioning
confidence: 99%